Predictive factors of developing type 2 diabetes mellitus, Acute Myocardial Infarction and stroke in a cohort with Impaired Fasting Glucose in Singapore. (October 2017) - Chia, Dennis Bingzhu; Wong, Lai Yin; Liu, Daveon Yu Kai; Toh, Matthias Paul Han Sim
Highlights: Key predictors are (1) age 40–49, (2) high BP of ≥140/90 mmHg (3) high BMI ≥27.5 kg/m 2 . Early identification of risk factors for screening may prevent these outcomes. Frequency of cardiovascular risk screening in Singapore could be increased. Abstract: Aims: This study describes the incidence and predictive factors for development of Type II Diabetes Mellitus (T2DM), Acute Myocardial Infarction (AMI) and stroke, among subjects with IFG over a five-year period. Methods: This is a retrospective cohort study of subjects with newly diagnosed IFG from the Singapore National Healthcare Group hospitals and primary care clinics from 1 January 2008 to 31 December 2010. Clinical data were collected over a five-year period from the date of diagnosis. Outcomes of interest were T2DM, AMI and stroke based on first occurrence of the ICD-9 diagnoses from the chronic disease registry. Demographic characteristics, laboratory tests, anthropometric measurements and medical history were adjusted for in the multivariate logistic regression. Results: Out of 2295 eligible subjects, 552(24.1%) developed at least one of the outcomes. 492(21.4%) developed T2DM, 20(0.9%) developed AMI and 62(2.7%) developed stroke. Predictive factors for development of any of the three outcomes included age 40–49 [Adjusted OR = 2.25; 95% CI 1.44–3.51], blood pressure of 140/90 mmHg and above [Adjusted OR = 1.62, 95% CI 1.26–2.10] and BMI of 27.5 kg/m 2 or more [Adjusted OR = 2.35; 95% CI 1.61–3.41]. Females were more likely to develop T2DM [Adjusted OR = 1.43; 95% CI 1.10–1.85] but less likely to develop AMI and/or stroke compared to males [Adjusted OR = 0.43; 95% CI 0.24–0.76]. Conclusions: Development of T2DM/AMI/stroke within the first five years of IFG is significantly high for subjects age 40–49 and those with high BMI. Frequency of cardiovascular risk screening, which is currently once every three years, could be increased.